Labeling of carcinoembryonic antigen-specific CAR-T cells with superparamagnetic iron oxide nanoparticles and in vitro magnetic resonance imaging - HE Kungao; JIANG Bo; GUO Mudan (陆军军医大学学报, 2024)
Objective To use superparamagnetic iron oxide nanoparticles (SPIONs) to label chimeric antigen receptor (CAR) T cells targeting carcinoembryonic antigen (CEA), and perform magnetic resonance imaging (MRI) to real time trace CEA CAR-T cells in vivo. Methods Appropriate amount of ferumoxytol, heparin sodium and protamine sulfate were mixed at high (ferumoxytol 100 μg/mL, heparin sodium 4 IU/mL, protamine sulfate 120 μg/mL), medium (ferumoxytol 50 μg/mL, heparin sodium 2 IU/mL, protamine sulfate 60 μg/mL), and low (ferumoxytol 25 μg/mL, heparin sodium 1 IU/mL, protamine sulfate 30 μg/mL) concentrations to form a SPIONs complex ferumoxytol/heparin/protamine (FHP), and then co-incubated with CEA CAR-T cells for cell labeling. The biocompatibility of FHP was detected by CCK-8 assay, EdU assay and flow cytometry. The uptake of FHP was detected by Prussian blue staining, and SPIONs content in the cells was quantitatively detected by inductively coupled plasma-mass spectrometry (ICP-MS). Flow cytometry was used to detect the lytic effect of FHP-labeled CEA CAR-T cells on tumor cells, and MRI was employed to scan FHP-labeled CEA CAR-T cells. Results FHP at high, medium, and low concentrations had no significant effect on the activity of CEA CAR-T cells, with cell activity above 100% determined by CCK-8 assay. DNA proliferation was above 94.3% in EdU assays. Prussian blue staining showed that CEA CAR-T cells could take FHP up, with the uptake increased with the increment of FHP concentration. ICP-MS showed that the intracellular Fe content was 440.23±189.36 ng/mL. Tumor cell killing experiment showed that FHP-labeled CEA CAR-T cells had excellent killing capability against tumor cells. MRI scans indicated that T2WI signals of FHP-labeled CEA CAR-T cells were significantly reduced with increasing FHP concentration (P < 0.01). Conclusion SPIONs complex FHP shows good biocompatibility and can effectively label CEA CAR-T cells. SPIONs complex FHP can be used as a magnetic marker for CEA CAR-T cells and a feasible MRI tracer for clinical application.